EVALUASI KESESUAIAN LAHAN DAN POTENSI PRODUKSI TANAMAN MANGGIS (Garcinia mangostana L.) DI KAB.50 KOTA - Juniarti Juniarti; Yulnafatmawita Yulnafatmawita; Sudewi Isminingsih (Jurusan Tanah Fakultas Pertanian Universitas Andalas, 2008)
This research discusses the land suitability of mangosteen field in Kab.50 Kota Kota Payakumbuh, predict production potential of mangosteen based on the climate suitability, soil and management its field. Composite soil sample is taken through drilling 0 – 60 cm which is carried out on research site. Quantitative model from FAO (1976) is used to evaluate the land suitability. This model combines enviromental data, climate and soil condition (soil physic and chemistry characteristic), so that production potential of field based on climate (Climate Production Potential = CPP) can be maesured quantitatively. By entering the real data of plant production, this model can predict the real plant production in a field (Land Production Potential = LPP). Result of this research shows that climate and physical condition of land are very suitability to grow mangosteen, and its level appropriateness is S1 (very suitability). Then, production potential 3 – 12 ton/ha/year can be increased to > 15 ton/ha/year if the management of land is improved.Key Words : Land suitability evaluation, Climatic Production Potential, Land Production Potential